Biologics targeted at TNF: design, production and challenges - Gatto, B. (Reumatismo, 2006)
Autoimmune diseases affect millions of people worldwide and, with more than 70 distinct types of pathologies associated with autoimmune processes, represent a wide and fast-moving area of research and clinical interest (1). Extensive preclinical research has focused on the regulation of cytokine expression with special interest in rheumatoid arthritis (RA), and this multidisciplinary effort has contributed to elucidate the roles of cytokines in this and other disabling autoimmune diseases. Tumor necrosis factor alpha (TNFa) emerged from these studies as a pivotal regulator of expression of other pro-inflammatory cytokines such as Interleukin-1 (IL-1) and Interleukin-6 (IL- 6) (2), thus becoming a key target for therapeutic intervention in a redundant cytokine environment...